Pull Factors For Cultural And Heritage Tourism Destinations: How To Attract Westerns To The East - Shokhrukhbek Rasulov Hasan o’g’li, Mekhriniso Rasulova Sobir qizi, Ermatov Tokhir Sharipjanovich, Nabiyev Elshod Ganievich (International Journal of Advanced Science and Technology, 2020)
Being one of the largest industries in the world, tourism created a large arena where the destinations are compelled to contend with one another, distinguishing themselves in different ways. This research examines the Pull factors that influence the British and other European potential travellers’ choice of a destination for culture and heritage tourism. With the use of qualitative in-depth interview, the list of Pull factors that affect travellers’ decisions in cultural and heritage tourism destination choice were extracted and grouped according to their qualities. The results are aimed to provide deep understanding of the customers’ needs in tourism industry and identification of pull factors are supposed to help to select the right positioning strategy for tourism marketers.